Why not? – Communicating stochastic information by use of unsorted frequency pictograms – a randomised controlled trial - Kasper, Jürgen (German Medical Science GMS Publishing House, 2011)
Objective: Statistical health risk information has been proven confusing and difficult to understand. While existing research indicates that presenting risk information in frequency formats is superior to relative risk and probability formats, the optimal design of frequency formats is still unclear. The aim of this study was to compare presentation of multi-figure pictographs in consecutive and random arrangements regarding accuracy in perception and vulnerability for cognitive bias. Methods: A total of 111 patients with multiple sclerosis were randomly assigned to two experimental conditions: patient information using 100 figure pictographs in 1) unsorted (UP group) or 2) consecutive arrangement (CP group).The study experiment was framed as patient information on how risks and benefit could be explained. The information comprised two scenarios of a treatment decision with varying levels of emotional relevance. Primary outcome measure was accuracy of information recall (errors made when recalling previously presented frequencies of benefits and side effects). Cognitive bias was measured as additional error appearing with higher emotional involvement. The uncertainty tolerance scale and a set of items to assess risk attribution were surveyed. Results: The study groups did not differ in their accuracy of recalling benefits, but recall of side effects was more accurate in the CP-group. Cognitive bias when recalling benefits was higher in the UP-group than in the CP-group and equal for side effects in both groups. Results were similar in subgroup analyses of patients 1) with highly irrational risk attribution 2) with experience regarding the hypothetical contents or 3) with experience regarding pictograph presentation of frequencies. Overall, benefit was overestimated by more than 100% and variance of recall was extremely high. Conclusions: Consecutive arrangement as commonly used seems not clearly superior to unsorted arrangement which is more close to reality. General poor performance and the corresponding high variance of recall might have clouded existing effects of the arrangement types. More research is needed with varying proportions and other samples.